The Implementation of Imitation Strategy to Increase the Students’ Ability in Writing Recount Text - Syaifullah Syaifullah; Helmarita Helmarita (ELT-Lectura, 2016)
The problem of this research is based on students ability in writing recount text at the eighth grade ofSMPN 21 Pekanbaru. Most of students faced difficulties in the areas of tenses or structure masteries, lack ofvocabulary, mechanical skills, organization, and the content of the text. The purpose of this research was toimprove students’ writing ability especially in recount text by using imitation strategy. The design used in thisresearch was Classroom Action Research (CAR) consisting of two cycles. There was an improvement ofstudents’ skill in writing, it can be seen from base score was 41,37, cycle I was 63,18 and in cycle II there wasimprovement to be 83,14. It was caused by some factors, those are teacher and students have relationship. The students interested toward the imitation strategy and students’ were motivated, and fun learning. In conclusion, imitation strategy could improve students’ writing ability and could achieve the minimum level of achievement of writing ability especially in recount text.